Urinary neutrophil gelatinase-associated lipocalin is associated with preeclampsia in a cohort of Turkish women - Semra Yuksel; Sefik Eser Ozyurek; Deniz Kanber Acar; Cagdas Ozdemir; Sebile Guler; Huseyin Kiyak; Ali Gedikbasi (Taylor & Francis Group, 2019)
Purpose: We investigated the optimal cut-off level for urinary neutrophil gelatinase-associated lipocalin (NGAL) in preeclamptic patients to confirm the diagnosis. Methods: Urinary NGAL concentrations were measured by specific enzyme-linked immunosorbent assay (ELISA). Results: Patients with preeclampsia had significantly higher urinary NGAL concentrations than controls (mean: 387 ng/ml vs. 188 ng/ml, respectively; P< 0.001). Using a cutoff value 252 ng/ml for urinary NGAL to confirm diagnosis of preeclampsia, sensitivity, and specificity were 92% and 91%, respectively. Conclusion: Urinary NGAL concentrations were significantly elevated in women with preeclampsia versus normotensive controls.